NEW TYPE HYPERBOLIC FRAMED SLANT HELICES IN HYPERBOLIC 3-SPACE - Bulut, Fatma; Bektas, Mehmet (Editura Bibliotheca-Bibliotheca Publ House, 2025)
In this paper, we introduce the notion of (k, m)-type slant helices in Hyperbolic 3-space. Using their Frenet-type formulas, we provide theories for hyperbolic framed curves. Also, we express the relationship between the (k, m)-type hyperbolic framed slant helices and their properties using the hyperbolic curvature.
Keywords: Hyperbolic 3-space; (k,m)-type hyperbolic framed slant helices; hyperbolic framed curves